Soul of the City: The Depth of How "Urban" Matters in the Sociology of Religion. (14th November 2017) - Emerson, Michael O; Knight Johnson, Lenore M
Abstract: Humanity is undergoing a fundamental, dramatic shift from a rural people to an urban people. Just as importantly, urban areas are growing ever larger. Despite sociology of religion's role to understand religion within the patterning of human societies, the field has largely ignored how the move to more and ever larger urban areas does and will shape religion. In this article, we present a framework for studying how urban matters. The framework, built from research on urban "laws" and forms, consists of four interlocking components: City Scale, Human Interaction, Diversity and Subcultures, and The Local. We outline each of these and suggest how they may be working to change the nature and content of religion among urban dwellers. We discuss the substantial need for research to test, revise, and continue building the framework if we are to understand how urban impacts religion.